The Relationship Between Halal Labeling and Product Design on Consumer Purchase Interest (Marketing Management Literature Review) - Maharani, Amalina (Green Publisher, 2022)
This study aims to examine The Relationship between Halal Labeling and Product Design on Consumer Purchase Interest (marketing management literature review). In this study, researchers used descriptive qualitative methods and library research. By reviewing previous articles that are relevant to this research. The results of this study are: 1) Halal Labeling related to Consumer Purchase Interest, and 2) Product Design related to Consumer Purchase Interest.